Prevalence of enteric viruses in wastewater in Egypt after the COVID-19 pandemic. (7th November 2022) - Abd-Elshafy, Dina Nadeem; Nadeem, Rola; Bahgat, Mahmoud Mohamed
Abstract: People's hygienic habits greatly affect the spreading rate of enteric viruses. After the COVID-19 pandemic, many people followed announced precautions and improved their hygienic status to protect themselves from SARS-CoV-2 infection. Here, we studied if this indirectly affected the prevalence of enteric viruses in Egypt. A total of 21 samples (one sample per week) were collected from the Zenin wastewater treatment plant (WWTP) through the period between August 2021 and March 2022. Detection of adenovirus, hepatitis A virus (HAV), and rotavirus showed their presence in 66, 14.3, and 9.5% of the collected samples, respectively. Comparing those percentages to previously published data concerned with the detection of the same viruses from the same WWTP or others revealed a remarkable decrease in the prevalence of the three viruses after the COVID-19 pandemic. This allows the conclusion that safety precautions against SARS-CoV-2 lead indirectly to a reduction of adenovirus, HAV, and rotavirus prevalence rates. HIGHLIGHTS: Safety precautions against SARS-CoV-2 lead indirectly to a remarkable reduction in the prevalence rates of enteric viruses. Prevalence of adenovirus decreased to 66% after the pandemic. Hepatitis A virus showed 14.3% positivity of tested samples. Rotavirus prevalence became 9.5% after the pandemic. All those prevalence percentages were remarkably less than detection percentage before the COVID-19 pandemic.